Targeted alpha therapy using short-lived alpha-particles and the promise of nanobodies as targeting vehicle. (2nd August 2016) - Dekempeneer, Yana; Keyaerts, Marleen; Krasniqi, Ahmet; Puttemans, Janik; Muyldermans, Serge; Lahoutte, Tony; D'huyvetter, Matthias; Devoogdt, Nick
ABSTRACT: Introduction : The combination of a targeted biomolecule that specifically defines the target and a radionuclide that delivers a cytotoxic payload offers a specific way to destroy cancer cells. Targeted radionuclide therapy (TRNT) aims to deliver cytotoxic radiation to cancer cells and causes minimal toxicity to surrounding healthy tissues. Recent advances using α-particle radiation emphasizes their potential to generate radiation in a highly localized and toxic manner because of their high level of ionization and short range in tissue. Areas covered : We review the importance of targeted alpha therapy (TAT) and focus on nanobodies as potential beneficial vehicles. In recent years, nanobodies have been evaluated intensively as unique antigen-specific vehicles for molecular imaging and TRNT. Expert opinion : We expect that the efficient targeting capacity and fast clearance of nanobodies offer a high potential for TAT. More particularly, we argue that the nanobodies' pharmacokinetic properties match perfectly with the interesting decay properties of the short-lived α-particle emitting radionuclides Astatine-211 and Bismuth-213 and offer an interesting treatment option particularly for micrometastatic cancer and residual disease.